Non-stochastic reassembly of a metabolically cohesive gut consortium shaped by N-acetyl-lactosamine-enriched fibers - Madison Moore; Hunter D. Whittington; Rebecca Knickmeyer; M. Andrea Azcarate-Peril; Jose M. Bruno-Bárcena (Gut Microbes)
Diet is one of the main factors shaping the human microbiome, yet our understanding of how specific dietary components influence microbial consortia assembly and subsequent stability in response to press disturbances – such as increasing resource availability (feeding rate) – is still incomplete. This study explores the reproducible re-assembly, metabolic interplay, and compositional stability within microbial consortia derived from pooled stool samples of three healthy infants. Using a single-step packed-bed reactor (PBR) system, we assessed the reassembly and metabolic output of consortia exposed to lactose, glucose, galacto-oligosaccharides (GOS), and humanized GOS (hGOS). Our findings reveal that complex carbohydrates, especially those containing low inclusion (~1.25 gL−1) components present in human milk, such as N-acetyl-lactosamine (LacNAc), promote taxonomic, and metabolic stability under varying feeding rates, as shown by diversity metrics and network analysis. Targeted metabolomics highlighted distinct metabolic responses to different carbohydrates: GOS was linked to increased lactate, lactose to propionate, sucrose to butyrate, and CO2, and the introduction of bile salts with GOS or hGOS resulted in butyrate reduction and increased hydrogen production. This study validates the use of single-step PBRs for reliably studying microbial consortium stability and functionality in response to nutritional press disturbances, offering insights into the dietary modulation of microbial consortia and their ecological dynamics.